Psychological Integration and Emotional Intelligence Among Female University Students - AlHaddad, Prof. Dr. Noor Hatem; KADHIM, Dr. AHMED QASIM; Arif, Zahraa Ali (Indonesian Journal of Education Methods Development, 2025)
General Background: Psychological integration and emotional intelligence are central psychological constructs associated with students’ personal adjustment and academic life within higher education environments. Specific Background: In colleges of physical education, female students encounter academic, social, and emotional demands that require balanced psychological integration and well-developed emotional intelligence. Knowledge Gap: Empirical evidence comparing these constructs between different academic stages among female university students remains limited, particularly within physical education contexts. Aims: This study aimed to compare levels of psychological integration and emotional intelligence between first- and fourth-stage female students in a college of physical education and sports sciences. Results: Descriptive and inferential analyses indicated no statistically significant differences in psychological integration between stages, while emotional intelligence scores were significantly higher among fourth-stage students. Novelty: The study provides stage-based comparative evidence on two key psychological characteristics within female physical education students at the university level. Implications: The findings support the use of psychological assessment tools across academic stages and highlight the importance of institutional psychological guidance to support students’ psychological and emotional development. Highlights: No significant stage-based differences were identified in students’ psychological integration. Senior students demonstrated higher emotional intelligence compared to first-stage students. Psychological assessment is relevant for supporting student development across academic stages. Keywords: Psychological Integration; Emotional Intelligence; Female University Students; Physical Education; Higher Education